PEMILU SERENTAK: DILEMA ANTARA PRAGMATISME DAN EFEKTIFITAS SISTEM PRESIDENSIAL - Maulana, Juliansyah Rahmat; Zandi, Andi Muhfi; Afra, Nada (Department of International Relations, Brawijaya University, 2019)
Abstract: The electoral system is one of the essential values of democracy. This system was intended to ideally accommodate people needs—Indonesia has been implemented the electoral system in 1955. Over decades, the implementation faces various challenges. In this paper, examine the electoral system that held in 2019 under the threatening circumstances toward democracy itself, such as, overspread of hoax news, and religion-based vote. The existence of coat tail effect in Indonesia’s election also being the highlight of this phenomenon.Kata Kunci: Coat tail effect, Demokrasi, Indonesia, Pemilihan Umum